Active System Control Design of System Resilience - Schagaev, Igor (Springer International Publishing, 2018)
This book introduces an approach to active system control design and development to improve the properties of our technological systems. It extends concepts of control and data accumulation by explaining how the system model should be organized to improve the properties of the system under consideration. The authors define these properties as reliability, performance and energy-efficiency, and self-adaption. They describe how they bridge the gap between data accumulation and analysis in terms of interpolation with the real physical models when data used for interpretation of the system conditions. The authors introduce a principle of active system control and safety-an approach that explains what a model of a system should have, making computer systems more efficient, a crucial new concern in application domains such as safety critical, embedded and low-power autonomous systems like transport, healthcare, and other dynamic systems with moving substances and elements. On a theoretical level, this book further extends the concept of fault tolerance, introducing a system level of design for improving overall efficiency. On a practical level it illustrates how active system approach might help our systems be self-evolving. Presents the rationale for, and theory of, redundancy, presented for easy application in system design; Describes the role of activeness in system design in terms of what is needed to making systems efficient; Estimates the benefit of using a new approach of active system control system.